O uso de investigações matemáticas na abordagem da semelhança de triângulos e aplicações - Cruz, Josinaldo dos Santos (2015)
This study aims to understand the importance of mathematical investigations in the study of similar triangles and their applications. Considering the importance of research activities for teaching and learning, this paper presents some de nitions , aspects and considerations of this teaching methodology . We speak also of the teacher's role and possible obstacles in carrying out investigative tasks. To this end, data was collected through the implementation of three investigative activities in a class of 9th grade of elementary school of a college of the state of Sergipe. The results show that the inclusion of research activities in the classroom everyday , at any level of education , indicates a better learning of the content studied.